The Potential of Local Wisdom on Traditional Fishing (Tangkul) Gear in Lake Sipin Jambi City as a Science Learning Source - Jufrida Jufrida; Fibrika Rahmat Basuki; Dwi Risky Pratiwi (Scientiae Educatia: Jurnal Pendidikan Sains, 2018)
This study aims to explore and identify the concept of science contained in â€œTangkulâ€ and mapping basic competence of science in Junior High School. The study was descriptive qualitative research. The research subjects were the Sipin Lake community and science education experts. The data collection instruments used were observation sheets, interview guides, and documentation. Data were analyzed descriptively using the Miles and Huberman analysis model (data collection, reduction, display, and verification). The validity test of the data used is the triangulation technique. Tangkul is a traditional fishing gear in Lake Sipin form of trap nets were hung using bamboo. The working mechanism of Tangkul uses the principle of a simple aircraft, namely a net as a load, a pole as support, bamboo as a power arm and a load arm. At the time of lifting the nets, the fishermen draw power with muscle force smaller than the load. The mapped basic competency is in class VIII, i.e., basic competency 3.3 Explain the concept of effort, simple plane, and its application in everyday life including muscle work on the structure of the human skeleton.